Pengaruh Kebijakan Hutang dan Profitabilitas terhadap Harga Saham dengan Kebijakan Dividen sebagai Variabel Moderasi - Windya Miransa; Sri Yuni (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
The goal of this research is to examine how dividend policy affects the link between debt policy and profitability on share prices (among LQ45 enterprises for the period 2019-2022). A quantitative methodology and secondary data in the form of annual reports were used to assemble the results of this research. We employed a purposeful selection method to choose 17 of the LQ45 companies that met our inclusion criteria. We use moderated regression analysis and multiple linear regression analysis to examine the data. The results of this research show that debt policy has no effect on stock prices, but profitability does. Stock prices may be cushioned from the effects of debt policy via dividend policy. Profits have more of an effect on share prices when combined with a payout policy of moderate generosity.